(untitled) (International Journal of Food and Nutritional Sciences, 2022)
Soil is one of the most significant ecological factors, on which plants depend for their nutrients, water and mineral supplementation. Soil is having living organisms and products of their decay intermingled, which plays a significant role and acts as a manure. The Present study is conducted to identify the possible impact of Sugar factory, near Purna city and its effluents on the soil nature. Analysis was carried out of few selected chemical parameters of soil, here we selected few soil nutrients. The effluents from sugar factory are they affecting the quality of soil, as we decided to investigate it. For the present study we have selected soil nutrients like sulphate, phosphate, nitrite-nitrogen and ammonia etc. A field study for soil and its various materials was carried out at surrounding farmland near Sugar factory at Purna, during the period January 2019 to December 2019. The soil is mainly alluvial in nature. The observed values of soil chemical characteristics were studied for causing pollution if any. Our objectives are to evaluate the chemical characteristics of this soil. Standard analytical methods were applied for soil analysis. The analysis of soil was carried out during entire year of 2019 and the expressed in respective units.